2020
DOI: 10.4143/crt.2019.007
|View full text |Cite
|
Sign up to set email alerts
|

SUVmax Predicts Disease Progression after Stereotactic Ablative Radiotherapy in Stage I Non-small Cell Lung Cancer

Abstract: Fluorodeoxyglucose positron emission tomography-computed tomography (PET-CT) is gaining evidence as a predictive factor in non-small cell lung cancer (NSCLC). Stereotactic ablative radiotherapy (SABR) is the standard treatment in early-stage NSCLC when a patient is unsuitable for surgery. We performed a study to assess the prognostic clinical significance of PET-CT after SABR in early-stage NSCLC. Materials and Methods Seventy-six patients with stage I NSCLC treated with SABR were investigated. Total radiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
0
3
2
Order By: Relevance
“…We con rmed clinical stage to be univariate risk factors in the present study, whilst location, tumor T stage, node metastasis were not signi cant risk factors in our univariate analysis [26,27]. These ndings do not agree with previous reports that tumor T stage is risk factors for the outcome in early NSCLC patients [28] which may be due to the small size of study population.…”
Section: Discussioncontrasting
confidence: 85%
“…We con rmed clinical stage to be univariate risk factors in the present study, whilst location, tumor T stage, node metastasis were not signi cant risk factors in our univariate analysis [26,27]. These ndings do not agree with previous reports that tumor T stage is risk factors for the outcome in early NSCLC patients [28] which may be due to the small size of study population.…”
Section: Discussioncontrasting
confidence: 85%
“…We confirmed clinical stage to be univariate risk factors in the present study, whereas location, tumor T stage, and node metastasis were NS risk factors in our univariate analysis [26,27]. These findings do not agree with previous reports that the tumor T stage is a risk factor for the outcome in early NSCLC patients [28], which may be due to the small size of the study population.…”
Section: Discussioncontrasting
confidence: 81%
“…18 FDG-PET/CT, which is a tool to evaluate tumor metabolism and reveal the uptake of FDG by tumor cells, has been applied widely for early detection of tumor locations and the decision-making of anticancer intervention. Some previous studies have reported that several baseline parameters derived from PET/CT before initiation of treatment, such as SUVmax and SUVmean might predict clinical treatment response and recurrence in patients with various types of human cancers [28][29][30][31][32] . A previous retrospective study of stage III NSCLC patients showed that SUVmax signi cantly affected the OS of patients with NSCLC, which is consistent with our nding that the patients with a higher SUVmax (SUVmax ≥ 14) had a worse OS than those with a lower SUVmax (SUVmax < 14) (median of OS: 18 months vs. 25 months) after de nitive chemoradiotherapy 33 .…”
Section: Discussionmentioning
confidence: 99%